Microbiological Identification and Characterization of Pathogenic Bacteria in Garri Sold within the University of Benin - Aghemwenhio, Itohan Sandra; Chukwu, Favour Ogochukwu; Ogbebor, Vivian; Akeem, Sarafa Adeyemi (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Garri is one of the processed cassava products. It is a staple cuisine for most people in southern Nigeria and is consumed widely throughout West and Central Africa. Nigeria alone produces an estimated ten million tons annually. Processing conditions and storage containers have the ability to act as growth enhancers for bacteria and fungi, resulting in microbial contamination of garri. Pathogenic bacteria and opportunistic pathogens can create toxins and other metabolites that can result in infectious diseases, which are one of the main causes of death globally each year. For this reason, it is crucial to have extremely sensitive, specific, and quick approaches for identifying and managing foodborne infections as possible health hazards. In the University of Benin, the student market (June 12 market) is the place where different foodstuffs like rice, beans, yams, garri etc are made available for students’ consumption and the hygiene practices of the market sellers is of great concern. Data on the attitude and knowledge regarding hygiene and sanitation level of the food handlers actively selling in the market was unknown, hence the need to conduct a research on the hygiene, sanitation and microbiological quality of the food handlers in the market, (June 12 market) University of Benin. The following bacteria , B. cereus, Salmonella, Shigella, E. coli were isolated from garri samples obtained from the student market at the University of Benin. The findings of the observation indicated that there were a lot of pathogenic bacteria in the food sample (garri), which may have been caused by the market workers’ poor hygiene and sanitization standards, as well as those of the distributors and processors. These bacterial pathogens can be prevalent in a particular geographical location though they could arise anywhere based on hygiene standard of food handlers at all levels.